The Legal Framework in Addressing Modern Slavery and Human Trafficking a Focus on Indonesia - Harsya, Rabith Madah Khulaili; Zuwanda, Zulkham Sadat (Eastasouth Institute, 2024)
The legal, sociological, and practical aspects of stopping human trafficking and modern slavery in Indonesia are examined in this study. The study uses a mixed-methods approach, combining in-depth interviews with key informants from several sectors participating in anti-trafficking operations with normative analysis. The interviews provide rich insights from legal experts, law enforcement authorities, government representatives, NGOs, judicial staff, journalists, international organizations, and social workers; the normative analysis highlights the advantages and disadvantages of Indonesia's legal system. The results highlight difficulties such as a lack of resources, problems with coordination, and socioeconomic variables that increase susceptibility. Regular evaluations of the legal framework, improved coordination, victim-centric strategies, responsible media coverage, and international cooperation are among the recommendations. This study adds to the larger conversation about preventing human trafficking by providing a thorough grasp of the complex issues and viable solutions in the Indonesian setting.